+0  
 
0
291
2
avatar+6 

y = -1, -9x – 3y = -6

aacer28  Apr 25, 2017
edited by aacer28  Apr 25, 2017
 #1
avatar+6 
0

x=1 and y=-1

aacer28  Apr 25, 2017
 #2
avatar+54 
+2

-9x - 3(-1) = -6

-9x + 3 = -6

-9x = -9

x = 1

Doboman  Apr 25, 2017

6 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.